Developing a coding scheme for analysing classroom dialogue across educational contexts. (June 2016) - Hennessy, Sara; Rojas-Drummond, Sylvia; Higham, Rupert; Márquez, Ana María; Maine, Fiona; Ríos, Rosa María; García-Carrión, Rocío; Torreblanca, Omar; Barrera, María José
Abstract: The research reported sought to develop a framework for systematically analysing classroom dialogue for application across a range of educational settings. The paper outlines the development and refinement of a coding scheme that attempts to represent and operationalise commonalities amongst some key theorists in the field concerning productive forms of educational dialogue. The team has tested it using video recordings from classroom settings in the UK and Mexico, across age phases, subject areas, and different interactional contexts including whole class, group and paired work. Our Scheme for Educational Dialogue Analysis (SEDA) is situated within a sociocultural paradigm, and draws on Hymes' Ethnography of Communication to highlight the importance of context. We examined how such a tool could be used in practice. We found that concentrating on the 'communicative act' to explore dialogue between participants was an appropriate level of granularity, while clustering the 33 resulting codes according to function of the acts helped to highlight dialogic sequences within lessons. We report on the application of the scheme in two different learning contexts and reflect on its fitness for purpose, including perceived limitations. Development of specialised sub-schemes and a version for teachers is underway.